2004
DOI: 10.1158/1078-0432.ccr-04-0063
|View full text |Cite
|
Sign up to set email alerts
|

Increased Angiogenesis and Lymphangiogenesis in Inflammatory versus Noninflammatory Breast Cancer by Real-Time Reverse Transcriptase-PCR Gene Expression Quantification

Abstract: Results: Inflammatory breast cancer specimens had significantly higher mRNA expression levels than noninflammatory breast cancer specimens of the following genes: KDR (P ‫؍‬ 0.033), Ang-1, (P ‫؍‬ 0.0001), Tie-1 (P ‫؍‬ 0.001), Tie-2 (P ‫؍‬ 0.001), FGF-2 (P ‫؍‬ 0.002), VEGF-C (P ‫؍‬ 0.001), VEGF-D (P ‫؍‬ 0.012), Flt-4 (P ‫؍‬ 0.001), Prox-1 (P ‫؍‬ 0.005), and LYVE-1 (P ‫؍‬ 0.013). High mRNA levels of FGF-2 and cyclooxygenase-2 corresponded to increased protein expression by immunohistochemistry. Inflammatory brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
1
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 206 publications
(149 citation statements)
references
References 24 publications
6
137
1
4
Order By: Relevance
“…As such it was of interest to examine if these lymphatics were newly formed or were pre-existing. In the study of Van der Auwera et al [20]. Ki-67-positive LECs were detected in 16 (*50%) noninflammatory and 12 (80%) inflammatory specimens whereas the study by van der Schaft et al [39] reported no proliferative LECs (10 specimen were studied).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…As such it was of interest to examine if these lymphatics were newly formed or were pre-existing. In the study of Van der Auwera et al [20]. Ki-67-positive LECs were detected in 16 (*50%) noninflammatory and 12 (80%) inflammatory specimens whereas the study by van der Schaft et al [39] reported no proliferative LECs (10 specimen were studied).…”
Section: Discussionmentioning
confidence: 93%
“…No standard method is currently used for the assessment of the proliferation fraction of lymphatics (PF-L) in human tumours. Different approaches have been used with certain studies simply reporting the presence or absence of MIB-1 positive LEC nuclei [35], with others reporting the number of positive nuclei/100 LECs nuclei [20], and yet others counting the number of positive nuclei in three high power fields [21]. As both the proliferation fraction of the tumoural lymphatics (PF-L) and of the tumour emboli (PF-E) were to be assessed, specimens which had LVI were selected for the double IHC procedure; they were 54 specimens of which 41 specimens were characterized with high LVD.…”
Section: Assessment Of Lymphangiogenic and Angiogenic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others had shown that intratumoral lymphatics with tumor emboli do exist; however, most of the LI lesions are located in peritumoral vessels. 8,[29][30][31] We have also examined whether the frequency of LI per tumor tissue affects outcome in LN-positive tumors. In our previous study assessing LI in 1000 LN-negative BC, number of LI foci ranged from 1 to 79 per tumor section.…”
Section: Discussionmentioning
confidence: 99%
“…Expression was assessed by grading each section on staining intensity with subjective scores ranging from 0 to 3, 0 -negative, 1 -weak, 2-moderate and 3 -strong expression as per previous published studies ( Van der Auwera et al, 2004). For VEGF, a cumulative score from the four sites of staining was calculated and stratified for analysis (0-3, 4-7, 8-12).…”
Section: Quantitative Analysis Of Lymphatic Vessel Blood Vessel Densmentioning
confidence: 99%